Fundamental Investigation on Seismic Retrofitting Method of Aging Concrete Structural Wall Using Carbon Fiber Sheet-Constitutive Law of Rectangular Section - Kazuhiro Hayashi; Tomoya Matsui; Taiki Saito; Roy Reyna (Advances in Materials Science and Engineering)
Aging building structure has become a world problem. This problem is particularly serious in developing and underdeveloped countries. The multihazard resilience and sustainability (e.g., seismic performance) decrease at the aging building. A construction method for strengthening aging-reinforced concrete buildings by wrapping structural members with carbon fiber sheets has been proposed and implemented in recent years. Authors aim to develop a seismic retrofitting method of aging concrete structural wall with a rectangular cross section using carbon fiber sheets. In this paper, authors examined the stress-strain relationship of concrete elements with rectangular cross sections reinforced by wrapping with carbon fiber sheets. Monotonic uniaxial compression tests were performed on 21 specimens using the ratio of the long side to the short side and the ratio of the element height to the short side of the concrete cross section, the weight of the carbon fiber sheet, and the chamfer radius of section corners as variables. The tests revealed that (1) the compressive strength decreases and ultimate strain increases as the ratio of the long to short side (longitudinal ratio) of the cross section increases even in a range the ratio exceeds 2 and (2) the ratio of the element height to the short side does not significantly affect the stress-strain relationship. Furthermore, authors proposed evaluation formulas for the constitutive law of concrete elements with rectangular cross sections including the longitudinal ratio which exceeds 2 reinforced by carbon fiber sheets and confirmed that the formulas can reproduce the test results with good accuracy.